PMM.25 Outcomes in women with thrombocytopenia in pregnancy. (9th June 2014) - Aiyelaagbe, S; Hobson, M; Byrd, LM; Tower, CL
Abstract : Background: Antenatal thrombocytopenia occurs in 5% of pregnancies and is predominantly due to gestational thrombocytopenia (GTP), or more rarely is immunologically-mediated (ITP). The risk of significant neonatal thrombocytopenia (<50 × 10 9 /L) has been suggested as 5–10% in women with ITP, although risk of bleeding is low. The aim of this study was to report pregnancy outcomes of women with thrombocytopenia in a large UK tertiary referral centre. Methods: Pregnant women with platelet counts ≤ 120 × 10 9 /L were identified retrospectively from the laboratory records between December 2011 and December 2012. Pregnancy and neonatal records were examined and data collected. Results: Laboratory records identified 215 women with a platelet count ≤ 120 × 10 9 /L during pregnancy. 118/215 (55%) were excluded due to pre-eclampsia, sepsis or post-partum haemorrhage. 100 infants were born to 97 women, 25 (26%) delivered by Caesarean section. 17 had presumed GTP, 30 ITP, with 50 being of unknown cause antenatally. 10/98 (10.2%) had a blood loss greater than 1000mls, comparable to the hospital population (9.2%). Neonatal platelet counts were available 69/101(68%) babies. 19/69 (27.5%) had thrombocytopenia <150 × 10 9 /L, with 3 (4.3%) <50 × 10 9 /L. There was one report of a small non-significant intraventricular haemorrhage (platelets 12 × 10 9 /L). Maternal platelet count did not correlate with either blood loss or neonatal platelet count. Conclusions: Whilst neonatal thrombocytopenia was relatively common (27.5%), clinically significant neonatal thrombocytopenia was rare which is reassuring for women. Low maternal platelets did not increase the risk of postpartum haemorrhage.